Small Medium Enterprises Insurance Credit Risk Management - Kobjaiklang, Chulaporn N; Rojsurakitti, Terdsak (Archives of Business Research, 2015)
Thai SMEs have played a vital role in the Thailand economy. However, SME has structure of short term financial characteristics as they depend mostly on short term loan. Thus, we have to be aware of financial distress of SMEs. The study has examined empirical evidence from Thailand insurance industries to identify differences between financial profiles of financially distressed SMEs and non-financially distressed SMEs. We have developed and tested a multiple discriminant analysis model to distinguish between financially distressed SMEs and non-financially distressed SMEs using three categories of financial ratios: liquidity, leverage and profitability. The results show that distressed firms SMEs had lower liquidity, higher leverage and lower profitability ratios than non-financially distressed SMEs. Study tested the statistical significance of the differences between financially distressed SMEs and non-financially distressed SMEs. The financial ratios of distressed firms were taken into the analysis to develop the prediction model. Keywords: SMEs, financially distressed SMEs, non-financially distressed SMEs, liquidity, leverage, and profitability